Communication 2.0 to promote tourism in Iberoamerica: Analysis of government web portals and social networks [Comunicación 2.0 para la promoción turística en Iberoamérica: Análisis de portales web y redes sociales gubernamentales] - Paladines Galarza, F. (2015)
Internet and social networks are the ideal platform for tourism promotion and dissemination, as it has become the main source of information on which merges the supply and demand of countless tourist destinations. These spaces have been used by government tourism agencies in Latin America, due to the cultural and natural diversity that they possess, they have gotten through communication campaigns 'on and offline' to promote new destinations in the international market, deriving in significant economic growth. This research analyzes how government agencies, promote each of the countries, the offer presented and interactive platforms used, because at present the main features of web are the interaction and user participation.